2016
DOI: 10.21037/jtd.2016.09.07
|View full text |Cite
|
Sign up to set email alerts
|

Extensive plastic bronchitis: etiology of a rare condition

Abstract: We present the case of a 55-year-old man who developed extensive occlusive bronchial casts after trachea-esophageal (TE) fistula repair. The bronchial casts were treated by bronchoscopic extraction, high dose steroids, antibiotics, and antifungals. Despite this multi-modality treatment, the rapid formation of these occlusive bronchial casts was very aggressive and could not be controlled even with a series of five rigid bronchoscopic extractions within a 48-hour period. The patient quickly deteriorated and suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Sickle cell acute chest syndrome has been well described in a paediatric series of 21 patients with plastic bronchitis [23]. A similar presentation is described in a 19-year-old patient with sickle cell acute chest syndrome; however, the underlying pathophysiology remains unknown [24].…”
Section: Haematological Conditionsmentioning
confidence: 78%
See 1 more Smart Citation
“…Sickle cell acute chest syndrome has been well described in a paediatric series of 21 patients with plastic bronchitis [23]. A similar presentation is described in a 19-year-old patient with sickle cell acute chest syndrome; however, the underlying pathophysiology remains unknown [24].…”
Section: Haematological Conditionsmentioning
confidence: 78%
“…Iatrogenic causes of cast formation such as radiation or surgical trauma leading to probable lymphatic disruption have also been reported [23,30,31]. Plastic bronchitis has also been reported in a post-lung transplant patient with primary graft dysfunction on ECMO.…”
Section: Miscellaneous Conditionsmentioning
confidence: 96%
“…In a literature review, only one case of PB after thoracic surgery has been reported [ 14 ]. In that case, a 55-year-old man who developed an extensive occlusive bronchial cast after tracheal esophageal fistula repair and died of secondary severe ARDS and uncontrollable infection despite treatment with bronchoscopic extraction, steroids, antibiotics, and antifungals.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, bronchial cast type II is acellular and frequently seen in patients with underlying cardiac disease. 2 SUPPLEMENTAL ONLINE MATERIAL Supplemental material can be found online at http://www.mayoclinicproceedings.org. Supplemental material attached to journal articles has not been edited, and the authors take responsibility for the accuracy of all data.…”
mentioning
confidence: 99%